Application of smectitic clays from Porto Santo’ island in facial masks - Pena-Ferreira, Maria Rosa; Santos, Delfim; Silva, João Baptista Pereira; Amaral, Maria Helena; Sousa-Lobo, José Manuel; Gomes, Jorge Hamilton; Gomes, Celso de Sousa Figuerido (Anales de Hidrología Médica, 2012)
Clay minerals have been used for therapeutic and cosmetic purposes. Due to their ability to absorb impurities,to promote cell renewal and to prevent skin ageing, clay minerals enter into the composition of cosmetic products, for instance, in facial masks The goal of the present paper was the development of facial masks showing hydrating, adstringent, and anti-seborrhoeic properties, based on smectitic clays from Porto Santo’ island, with distinctive granularities. Both physical and mechanical properties corresponding to the distinctive formulations of facial masks being prepared were assessed in order to identify the one exhibiting better performance. Also, cutaneous biometric tests (determination of pH, of lipids content and hydration grade) were performed in order to characterize the formulations efficacy for application in dermocosmetics. The obtained results have shown a significant increase of the apparent viscosity when the clay incorporated into the masks shows the lower granularity. Therefore, we could conclude that the clay granularity less than
Keywords: Clay; Facial masks; Cutaneous biometric tests